Production of pleurotus sajor-caju on sawdust of rubber tree and empty palm fruit bunch - Muhamad, Ida Idayu; Hassan, M. F.; Mohamad, S. N. H.; Tin, L. C.; Sarmidi, M. R. (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
Cultivations of the grey oyster mushroom, Pleorotus sajor-caju , empty palm fruit bunch (EPFB), and combination of sawdust and EPFB (1:1; w/ w) without any nutrient supplementation were studied. The effects of different types of media on mushroom yield, time taken for mushroom growth, nutrient content in media and mushroom, and water activity were compared. The sawdust media yielded about 25% more mushrooms than EPFB under similar cultivation condition. However, mushroom failed to bloom fruit from the combination media of sawdust and EPFB. Mushroom grew in the sawdust media 28 days faster than EPFB media. The water loss of the media after mushroom growth varied from 44.6% to 40.2% and 51.2% to 32% for sawdust and EPFB media, respectively.